Clima social familiar y desarrollo psicomotor en escolares - Fernández Silva, María Alejandra (2018)
The current quantitative, descriptive and correlational research was developed in San Francisco de Asís N° 80038 educational institution, located in La Esperanza district, with the purpose of establishing the relationship between the level of social familiar atmosphere and the psychomotor development on elementary school students (5th grade). The sample included 87 students and two instruments were applied: social – familiar atmosphere scale and short pattern registration sheet. The Spearman correlation was considered to measure the existence and relationship level among variables. Results show that the higher percentage of students (69%) shows medium social familiar atmosphere, 28 percent low and only 3 percent shows a high percentage. With respect to the psychomotor development, the higher percentage (56%) shows a normal level and 44 percent shows a deficit. There’s a highly significant relationship between the level of social – familiar atmosphere and psychomotor development (p<0.01).